Factors related to stress in health professionals in the fight against the COVID-19 pandemic (Research, Society and Development, 2022)
This is an integrative literature review, which consists of summarizing and analyzing research results. To respond to the proposed objective, the following databases were consulted: Web of Science (Clarivate Analytics), Google academic, Medical Publications (PubMed), Scopus (Elsevier) and Scientific Electronic Library Online (SciELO). The following terms were used in the databases: health professional, pandemic, COVID-19, coronavirus and mental health, within the time frame from 2019 to 2021. The final study sample consisted of fifteen articles that met the proposed study object. In the analyzed literature, different approaches aimed at minimizing stress in the work environment were considered, given the complexity of the phenomenon investigated. Among the strategies capable of alleviating stress in a pandemic situation are those related to the environment and working hours, such as the creation of systems capable of managing the stress of professionals, flexibilization of working hours and support for professionals and their families. The study is important because, based on the knowledge of the factors that trigger the occupational stress of these professionals, it identifies strategies that aim to minimize the occurrence of this event.